The magnitude of neuromuscular fatigue is not intensity-dependent when cycling above critical power but relates to aerobic and anaerobic capacities - Schäfer, L. U.; Hayes, M.; Dekerle, J. (Experimental Physiology, 2019)
The aim of the present study was to test whether the development of neuromuscular fatigue within the severe intensity domain could be linked to the depletion of the curvature constant (W') of the power-duration relationship. Twelve recreationally active men completed tests to determine VO2peak, Critical Power (CP) and W', followed by two randomly assigned constant-load supra-CP trials set to fully deplete W' in 3 (P-3) and 12 min (P-12). Pre- to post-exercise changes in maximal voluntary contraction (MVC), potentiated quadriceps twitch force evoked by single (Qpot) and paired high- (PS100) and low-frequency (PS10) stimulations and voluntary activation (VA) were determined. Cycling above CP reduced MVC (P-3: -20 ± 10% vs. P-12: -15 ± 7%), measures associated with peripheral fatigue (Qpot: -35 ± 13% vs. -31 ± 14%; PS10: -38 ± 13% vs. -37 ± 17%; PS100: -18 ± 9% vs. -13 ± 8% for P-3 and P-12, respectively) and VA (P-3: -12 ± 3% vs. P-12: -13 ± 3%) (P < 0.05), with no significant difference between trials (P > 0.05). Changes in MVC and evoked twitch forces were inversely correlated with CP and VO2peak following P-12, while W' was significantly correlated with changes in Qpot and PS10 following P-3 (P < 0.05). Therefore, the magnitude of neuromuscular fatigue does not depend on exercise intensity when W' is fully exhausted during severe intensity exercise, yet exploration of inter-individual variations suggests that mechanisms underpinning exercise tolerance within this domain differ between short- vs. long-duration exercise.